La chronique des arts - Anonymus, A.
Neuerwerbungen, spez. Nr. 39 (p. 8): bouquetin, bronze, Iran, VIIe s. av. J.-C. (Museum für Kunst und Gewerbe, Hamburg); Nr. 91 (p. 19): idole féminine, Amlash, IIIe mill. (Musée de Mariemont, Belgique); Nr. 99 (p. 21): figure de femme, Marlik, 1200-100 av. J.-C. (The Montreal Museum of Fine Arts); Nr. 120 (p. 26): statuette de femme, Hacılar, 5400 av. J.-C. (Metropolitan Museum, New York); Nr. 270 (p. 67): fragment d’ivoire gravé en relief, Ziwiye, VIIe s. av. J.-C. (British Museum, Department of Western Asiatic Antiquities); Nr. 325 (p. 82): idole en terre cuite, Amlash, 1er mill. (Musée d’Art et d’Histoire, Genève).